TRANSFORMING ELEMENTARY EDUCATION: THE ROLE OF 21ST CENTURY SKILLS IN EVERYDAY LEARNING - Pratiwi, Irma (REKOGNISI : Jurnal Pendidikan dan Kependidikan (E-ISSN 2599-2260), 2024)
The transformation of primary education is an essential demand in today's digital era, particularly through the integration of 21st-century skills into daily learning. This study aims to examine the crucial role of 21st-century skills in primary school education. The research method used is a Systematic Literature Review (SLR), systematically analyzing 15 relevant journal articles and 5 books published between 2018 and 2024. These articles and books were analyzed based on their relevance to the integration of 21st-century skills in the context of primary education. The results indicate that 21st-century skills such as creativity, collaboration, communication, and critical thinking significantly enhance the quality of the learning process in primary schools. The implementation of these skills has been proven effective in improving students' learning motivation, strengthening their character, and increasing their readiness to face global challenges. Therefore, integrating 21st-century skills into daily learning becomes an essential solution for primary education to prepare a future generation that is more adaptive and innovative.